Comparison of Hematocrit Results Based on 1 Minute and 4 Minute Tourniquet Duration - Akbar, A Hafidatul Amanah; Aryandi, Rahmat; Muriyati, Muriyati (Journal of Multidiscipline and Collaboration Research, 2024)
This study aims to compare the results of hematocrit levels based on blood retention time for 1 minute and 4 minutes. The design of this study was an experimental laboratory with the subjects of the study being 3rd year D-III Medical Laboratory Technology students of STIKES Panrita Husada Bulukumba. A total of 17 samples were selected using a purposive sampling technique. The dependent variable of the study was hematocrit levels, while the independent variable was the duration of retention. Data analysis was performed using the Wilcoxon test through SPSS 20. The results showed that the average hematocrit level at 1 minute retention was 0.37%, while at 4 minutes retention it increased to 0.40%. Statistical analysis showed a significant difference between the two retention times with a p value = 0.000 (p <0.05). The increase in hematocrit levels at 4 minutes retention was caused by hemoconcentration due to the longer retention duration. The implication of this study is the need for consistency in retention time during blood sampling to prevent biased examination results.